Impact of pyrolysis conditions on polycyclic aromatic hydrocarbons (PAHs) formation in particulate matter (PM) during sewage sludge pyrolysis. (October 2018) - Ko, Jae Hac; Wang, Jingchen; Xu, Qiyong
Abstract: Polycyclic aromatic hydrocarbons (PAHs) not only present a risk to human health when released into the air, but also can be precursors to form particulate matter (PM) during sewage sludge pyrolysis. In this study, 16 EPA PAHs in PM (ΣPAHPM ) during sewage sludge pyrolysis were investigated with increasing temperature (200 o C–1000 °C) and holding time under different operation conditions [inert gas flow rate (IGFR) (200–800 mL/min) and heating rate (5–20 °C/min)]. ΣPAHPM varied with temperature, IGFR, and heating rate, and ranged from 597 (±41) μg/g to 3240 (±868) μg/g. ΣPAHPM decreased with increasing IGFR but increased with rapid heating rate. Among PAHs species in PM, naphthalene (Nap) was commonly detected at low temperature ranges in all tested conditions. Chrysene (CHR), benzo[ b ]fluoranthene (BbF), benzo[ k ]fluoranthene (BkF), benzo[ a ]pyrene (BaP), indeno[1, 2, 3-cd] pyrene (IND), and benzo[ g, h, i ]perylene (BghiP) in PM became abundant at high temperature with a low IGFR. At high temperature ranges with high volatile conditions (rapid heating rate and low IGFR), PAH formation and growth reactions were considerable, resulting in the formation of heavy PAHs in PM. Graphical abstract: Image 1 Highlights: PAHs formation depends on the operating conditions of pyrolysis. High inert gas flow rate lowered PAHs in PM. Rapid heating rates enhanced PAHs formation in PM. High temperature enhanced PAH formation and growth in PM.